Modification of the Daily Activity Pattern of the Diurnal Triatomine Mepraia spinolai (Hemiptera: Reduviidae) Induced by Trypanosoma cruzi (Trypanosomatida: Trypanosomatidae) Infection. Issue 6 (1st July 2021) - Pérez, G; Muñoz-San Martín, C; Chacón, F; Bacigalupo, A; Cattan, P E; Solís, R
Abstract: Mepraia spinolai, (Porter) 1934, is a diurnal triatomine endemic to Chile and a wild vector of the protozoan Trypanosoma cruzi, (Chagas) 1909, which causes Chagas disease. Behavioral changes in M. spinolai induced by this parasite have been reported previously, which include detection of a potential host, defecation latency, and some life history traits. In this study we assessed changes in locomotor and daily activity due to infection with T. cruzi . No difference was detected in distance traveled between infected and uninfected individuals. However, the groups differed in their daily activity patterns; infected individuals showed significant reduction of movements during the light phase and concentrated their activity in the dark phase. Uninfected individuals showed no differences in locomotor activity between the phases. The results suggest that T. cruzi induces a displacement in the activity of M. spinolai toward the dark phase of the circadian cycle, which may improve its vector competence.